2017
DOI: 10.3892/ol.2017.7121
|View full text |Cite
|
Sign up to set email alerts
|

TSLP promotes angiogenesis of human umbilical vein endothelial cells by strengthening the crosstalk between cervical cancer cells and eosinophils

Abstract: Abstract. Our previous study demonstrated that thymic stromal lymphopoietin (TSLP) secreted by cervical cancer cells promotes angiogenesis and recruitment, and regulates the function of eosinophils (EOS). However, the function of TSLP in the crosstalk between EOS and vascular endothelial cells in cancer lesions remains unknown. The aim of the present study was to investigate the effect of EOS caused by TSLP in in vitro angiogenesis of human umbilical vein endothelial cells (HUVECs). The results of the present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 39 publications
2
21
0
Order By: Relevance
“…Similarly, increased miR-205 was also previously observed in cervical squamous cell carcinoma cells . Consistently, Zhang et al (2017) revealed that miR-205 inhibited CC cell proliferation via olmesartan, which served as a therapeutic target for CC (Yue, Yun-Shan, & Feng-Xia, 2016). Meanwhile, a previous study demonstrated that poor expression of TSLC1 (also CADM1) was implicated in high risk HPV-mediated CC (Overmeer et al, 2008).…”
Section: Downregulation Of Mir-205 Suppresses Angiogenesis By Elevamentioning
confidence: 85%
“…Similarly, increased miR-205 was also previously observed in cervical squamous cell carcinoma cells . Consistently, Zhang et al (2017) revealed that miR-205 inhibited CC cell proliferation via olmesartan, which served as a therapeutic target for CC (Yue, Yun-Shan, & Feng-Xia, 2016). Meanwhile, a previous study demonstrated that poor expression of TSLC1 (also CADM1) was implicated in high risk HPV-mediated CC (Overmeer et al, 2008).…”
Section: Downregulation Of Mir-205 Suppresses Angiogenesis By Elevamentioning
confidence: 85%
“…Several studies reported a pro-tumor role for TSLP in cervical cancer (36)(37)(38). Tumor cells under hypoxia expressed TSLP, and TSLPR was expressed in both tumor cells and vascular endothelial cells.…”
Section: Cervical Cancermentioning
confidence: 99%
“…Notably, this finding might explain the concomitant presence of circulating DCs polarized into a tolerogenic phenotype, and the expanded T reg pool found in PDCA patients [ 4 , 6 ]. Moreover, TSLP produced by cervical cancer cells may promote angiogenesis [ 24 , 25 ], and down-regulate miR-132 expression, favoring tumor development [ 26 ]. The involvement of TSLP in tumor growth is also supported by several murine experimental studies, in which tumor growth was inhibited in TSLP-deficient hosts [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%